Effect of Electrode Material Variations on Wear Characteristics of Stir Cast A356/Red Mud/TiC Hybrid Metal Matrix Composite During Electrical Discharge Machining - Debasmita Pani; B. Surekha; Rishitosh Ranjan; Priyaranjan Samal; S. Rama Rao; Prakash Chandra Mishra (Tribology in Industry)
In the current study, an aluminum alloy A356-based hybrid metal matrix composite with red mud and titanium carbide reinforcements is fabricated using a liquid processing route namely the stir casting method. The machining characteristics along with the suitable electrode material during the electric discharge machining of the fabricated composite are determined. The authors are interested in studying the effects of various electric discharge machining (EDM) input parameters like peak current, the voltage on time, and gap voltage affecting the material removal rate (MRR) and tool wear rate (TWR) at the time of machining. Levels of input parameters to conduct the experiments are considered from the literature review, machine capacity, and pilot experiments. To predict the suitable electrode material for the newly fabricated heterogeneous composite material, different electrode materials namely brass, copper, graphite, and stainless steel are used to perform the experiments. Further, the surface roughness of the machined surface is measured and compared for different electrode materials used in the present work. From the results, it has been observed that copper electrode followed by stainless steel electrode show the least tool wear rate (TWR), while brass exhibited the highest TWR. Stainless steel electrode has shown a 90.73% reduction in TWR when compared with brass which has shown the largest TWR. But the Graphite electrode had shown a 57.19% improvement in MRR when compared with stainless steel which had produced a lower value of MRR.